ОЦІНКА ЕФЕКТИВНОСТІ ВИКОРИСТАННЯ ЕРДОСТЕЇНУ У ПАЦІЄНТІВ З COVID-19 - Дуда, О.К.; Вега, А.Р.; Манжелєєва, І.В.; Журавель, О.Д. (Українські медичні вісті, 2023)
ОЦІНКА ЕФЕКТИВНОСТІ ВИКОРИСТАННЯ ЕРДОСТЕЇНУ У ПАЦІЄНТІВ З COVID-19